The analysis of object-oriented metrics in C++ programs - Awang Abu Bakar, Normi Sham (IACSIT PRESS, 2014)
Software metrics play a very important role to develop good quality software. In today’s software development, object-oriented (OO) languages are used due to their basic features like class, object, information hiding, inheritance, encapsulation, abstraction and polymorphism. In addition, a number of object-oriented metrics are available to be used to measure the quality of the OO systems. One of the most popular OO metrics suite is the Chidamber and Kemerer (CK) metrics suite. The main focus of this research is to apply the CK metrics to a group of open source systems written in C++. The results show that only two out of six CK metrics, NOC and RFC are significant in predicting defects in the systems.